Comparison of Islamic and Conventional Bank Stock Portfolio Performance Using the Markowitz Model: Risk and Return Analysis on Four Selected Issuers - Aliffatul Laila; Asrie Putri Janitha (Research Collaboration Community (RCC), 2025)
This study aims to compare the performance of Islamic and conventional bank stock portfolios in Indonesia using the Markowitz Model approach that focuses on return and risk optimization. The object of research includes four banking issuers, namely BBCA and BBNI (conventional), and BRIS and BTPS (sharia), with daily closing price data during the period March 2020 to March 2021. Calculations were made on expected return, risk (standard deviation), sharpe ratio, and optimal portfolio composition. The results show that the Islamic stock portfolio has a higher expected return (0.009385) than the conventional portfolio (0.001652), but is accompanied by greater risk. Nevertheless, the efficiency of the Islamic portfolio remains competitive based on the sharpe ratio indicator and the ratio of return to variance. The optimal composition in the Islamic portfolio is dominated by BTPS stocks (68.69%), while in the conventional portfolio it is dominated by BBNI stocks (62.19%). These findings suggest that an Islamic bank stock portfolio can be an investment alternative that is not only ethical, but also financially superior in terms of risk and return.